Influence of selective laser treatment on thermal stability of Ti3AlC2 and Ti3AlC2/Cu powders; Materials Letters; Vol. 309 - Krinitsyn M. G. Maksim Germanovich; Ragulina M. P. Mariya Pavlovna; Firsina I. A. Irina Aleksandrovna; Travitsky (Travitzky) N. Nakhum (2022, 2022)
Title screen